Étude du colmatage des membranes en ultrafiltration et en coagulationultrafiltration d'eau de surface. Issue 2 (1st March 2003) - Bouchard, C; Sérodes, J; Rahni, M; Ellis, D; Laflamme, E; Rodriguez, M
Abstract : Ultrafiltration (UF) and coagulationultrafiltration (CUF) of raw water from the Des Roches Lake were performed and compared in terms of natural organic matter (NOM) removal and in terms of membrane permeability variation. The study was carried out at a laboratory scale with a membrane having a nominal pore size of 0.035 μμm. The removal of NOM by UF was significant (10% to more than 50% for UV absorbance at 254 nm and 0% to more than 30% for TOC) but was also very dependent on operating conditions. Membrane fouling occurred rapidly and was strongly accelerated as the permeate flux increased. Fouling also induced a decrease of NOM removal. Coagulation before UF brought a strong increase of NOM removal (TOC removal higher than 60% and reduction of UV absorbance at 254 nm higher than 80%). It also largely reduced membrane permeability loss even for permeation flux higher than 150 L·h 1 ·m 2 . In the absence of coagulation, and operating with full recirculation of the concentrate, there was a reduction of the SUVA ratio (UV254/TOC) and iron concentration in the feed water. This indicates a preferential deposit of humic substances onto the membranes and shows that iron either plays a role in membrane fouling or could be an indicator of the presence of fouling substances. Key words : ultrafiltration, coagulation, surface water, fouling, organic matter.